Cross linguistic influence of Malay language on English language acquisition / Francis Nyaun - Nyaun, Francis (2010)
This research considered the cross linguistic influence of Malay as the first language on English Language learning and acquisition. It was carried out in the Malaysian bilingual education system. The research was based on the concept of Common Underlying Proficiency (CUP) as proposed by Cummins and Swain (1989). It had been pointed out that all languages are sharing similar characteristics especially at conceptual level. The differences exist only at the surface level. This research was divided into two main parts. The first was the error analysis on the respondents’ written work, and second was the inferential statistics to do correlation and regression study. The data was obtained by carrying out error analysis and tagging of errors. The errors were grouped according to the categories. Frequency distribution and a cross linguistic study were carried out to determine whether Malay has positive or negative influence on English. The result of the study suggested that errors made in English were not solely because of the negative effects of Malay, rather, they were because of the learners weaknesses and incompetence. Inferential study was done to find out the correlation between Malay and English. The correlation study conducted shows the direction and magnitude of the two languages were positive and high moderate. The result of the regression shows that achievement for Malay could be used to predict achievement in English. To conclude, the ability and competence in one language could be used to learn and acquire second or subsequent languages.